Evaluation of the cytotoxic activities of the essential oil from Pistacia atlantica Desf. oleoresin on human gastric cancer cell lines - Saeedi, Fatemeh; Salehi, Mohammad; Kamali, Mohammad Javad; Mir, Mahsa Aghajani; Kazemi, Sohrab; Shirafkan, Fatemeh; Neyshaburi, Ebrahim Zabihi; Moeeni, Reihaneh; Gorji, Narjes; Memariani, Zahra (Medical oncology (Northwood, London, England), 2024)
Numerous herbal products have been the subject of research regarding their potential role in cancer prevention or adjuvant therapy. Pistacia atlantica and its main phytochemicals have garnered significant attention for their potential anti-cancer effects. The study aimed to assess the growth inhibitory effects of P. atlantica essential oil (PAEO) on MKN-45 and AGS cells. This study quantified the volatile compounds in PAEO using Gas Chromatography–Mass Spectrometry (GC–MS). Subsequently, MKN-45 and AGS cells were treated with varying concentrations of PAEO (5%, 2.5%, 1.25%, 0.625%, 0.3125%, 0.156%, 0.0781%, 0.0391%, 0.0195%) for 24 h. Cell viability was evaluated through the MTT assay. The impact of PAEO on gene expression was investigated by quantifying the mRNA levels of Bax and Bcl2 in the various experimental groups using quantitative Real-Time PCR (qRT-PCR) analysis. Additionally, flow cytometry was utilized to evaluate apoptosis in the treated cells. The analysis of PAEO revealed that α-pinene was the predominant monoterpene, constituting 87.9% of the oil composition. The cytotoxic effects of PAEO were evaluated, and it was found that the oil significantly reduced the viability of MKN-45 and AGS cells. The IC 50 for MKN-45 cells was determined to be 1.94 × 10 –3 % after 24 h of treatment, while for AGS cells the IC 50 was 2.8 × 10 –3 % after 24 h. Additionally, the research revealed that PAEO triggered a notable rise in apoptotic cells in both AGS and MKN-45 cell lines. Moreover, at the molecular level, the findings indicated an increase in Bax expression and a decrease in Bcl2 mRNA expression, providing further evidence of the induction of apoptosis in both MKN-45 and AGS cell lines following PAEO treatment. The findings of this study offer evidence supporting the cytotoxic effects of PAEO on gastric cancer cell lines by promoting apoptosis. The findings suggest that PAEO may offer potential as a therapeutic candidate in managing and treating gastric cancer.